Tumor-targeted polymeric nanostructured lipid carriers with precise ratiometric control over dual-drug loading for combination therapy in non-small-cell lung cancer - Liang Y (Dove Medical Press, 2017)
Yan Liang,1 Baocheng Tian,1 Jing Zhang,1 Keke Li,1 Lele Wang,1 Jingtian Han,1,* Zimei Wu2,* 1School of Pharmacy, Binzhou Medical University, 2School of Pharmacy, Yantai University, Yantai, China *These authors contributed equally to this work Abstract: Gemcitabine (GEM) and paclitaxel (PTX) are effective combination anticancer agents against non-small-cell lung cancer (NSCLC). At the present time, a main challenge of combination treatment is the precision of control that will maximize the combined effects. Here, we report a novel method to load GEM (hydrophilic) and PTX (hydrophobic) into simplex tumor-targeted nanostructured lipid carriers (NLCs) for accurate control of the ratio of the two drugs. We covalently preconjugated the dual drugs through a hydrolyzable ester linker to form drug conjugates. N-acetyl-D-glucosamine (NAG) is a glucose receptor-targeting ligand. We added NAG to the formation of NAG-NLCs. In general, synthesis of poly(6-O-methacryloyl-d-galactopyranose)–GEM/PTX (PMAGP-GEM/PTX) conjugates was demonstrated, and NAG-NLCs were prepared using emulsification and solvent evaporation. NAG-NLCs displayed sphericity with an average diameter of 120.3±1.3 nm, a low polydispersity index of 0.233±0.04, and accurate ratiometric control over the two drugs. A cytotoxicity assay showed that the NAG-NLCs had better antitumor activity on NSCLC cells than normal cells. There was an optimal ratio of the two drugs, exhibiting the best cytotoxicity and combinatorial effects among all the formulations we tested. In comparison with both the free-drug combinations and separately nanopackaged drug conjugates, PMAGP-GEM/PTX NAG-NLCs (3:1) exhibited superior synergism. Flow cytometry and confocal laser scanning microscopy showed that NAG-NLCs exhibited higher uptake efficiency in A549 cells via glucose receptor-mediated endocytosis. This combinatorial delivery system settles problems with ratiometric coloading of hydrophilic and hydrophobic drugs for tumor-targeted combination therapy to achieve maximal anticancer efficacy in NSCLC. Keywords: polymer–drug conjugate, nanostructured lipid carriers, combination treatment, ratiometric drug loading, cancer targeting